Process Oriented Guided Inquiry Learning dalam Mereduksi Miskonsepsi Siswa SMA pada Materi Kesetimbangan Kelarutan - Maria - Erna; Sri Haryati; Anggie Oktaviani S (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2021)
Abstract:The application of the Process Oriented Guided Inquiry Learning (POGIL) strategy was carried out to reduce students' misconceptions on solubility equilibrium material. The design of this experimental study was a randomized control group pretest-posttest. The evaluation instrument used is a three-tier multiple-choice test using the Certainty of Response Index. The population of this study was 11-grade students one of the public schools in Pekanbaru city. The study sample was determined randomly after the normality test and homogeneity test was carried out. The experimental class was treated with the application of the POGIL learning strategy while the control class was without the implementation of the POGIL strategy. Data analysis for hypothesis testing is done using the right-party t-test. The results showed that tcount <ttable (-0.59 <2.02) can be interpreted that the application of the POGIL strategy can reduce students' misconceptions in the solubility equilibrium material with a reduction in misconceptions by 47.05%.Abstrak:Penerapan strategi Process Oriented Guided Inquiry Learning (POGIL) dilakukan untuk mereduksi miskonsepsi siswa pada materi kesetimbangan kelarutan.  Rancangan penelitian eksperimen ini adalah randomized control group pretest-posttest. Instrumen yang digunakan adalah tes pilihan ganda tiga tingkat dengan menggunakan Certainty of Response Index. Populasi penelitian ini adalah siswa kelas XI salah satu sekolah negeri di kota Pekanbaru.  Sampel penelitian ditentukan secara acak setelah dilakukan uji normalitas dan uji homogenitas. Kelas eksperimen diberi perlakuan dengan penerapan strategi pembelajaran POGIL sedangkan kelas kontrol tanpa penerapan strategi POGIL. Analisa data untuk pengujian hipotesis dilakukan menggunakan uji-t pihak kanan. Hasil penelitian memperlihatkan thitung < ttabel ( -0,59 < 2,02) dapat diartikan bahwa penerapan strategi POGIL dapat mereduksi miskonsepsi siswa pada materi kesetimbangan kelarutan dengan reduksi miskonsepsi sebesar 47,05 %.